In vivo analysis of neuroinflammation in the late chronic phase after experimental stroke. (30th April 2015) - Walter, H.L.; Walberer, M.; Rueger, M.A.; Backes, H.; Wiedermann, D.; Hoehn, M.; Neumaier, B.; Graf, R.; Fink, G.R.; Schroeter, M.
Graphical abstract: USPIO-MRI revealed macrophages after stroke (red). Combined analysis with [ 11 C]PK11195-PET presented dominance of non-phagocytic neuroinflammation in the acute phase and increasing phagocytic activity in the chronic phase after stroke. Tissue affected by phagocytic activity, was associated with severe injury and necrosis. Highlights: Induction of pMCAO in rats by the macrosphere model. In vivo analysis of neuroinflammation until day 56. Imaging by USPIO-MRI and [ 11 C]PK11195-PET. Quantification of phagocytic activity and other inflammatory processes. Prediction of tissue fate. Abstract: Background and purpose: In vivo imaging of inflammatory processes is a valuable tool in stroke research. We here investigated the combination of two imaging modalities in the chronic phase after cerebral ischemia: magnetic resonance imaging (MRI) using intravenously applied ultra small supraparamagnetic iron oxide particles (USPIO), and positron emission tomography (PET) with the tracer [ 11 C]PK11195. Methods: Rats were subjected to permanent middle cerebral artery occlusion (pMCAO) by the macrosphere model and monitored by MRI and PET for 28 or 56 days, followed by immunohistochemical endpoint analysis. To our knowledge, this is the first study providing USPIO-MRI data in the chronic phase up to 8 weeks after stroke. Results: Phagocytes with internalized USPIOs induced MRI-T2 ∗ signal alterations in the brain. Combined analysis with [ 11 C]PK11195-PET allowed quantification of phagocytic activity and other neuroinflammatory processes. From 4 weeks after induction of ischemia, inflammation was dominated by phagocytes. Immunohistochemistry revealed colocalization of Iba1+ microglia with [ 11 C]PK11195 and ED1/CD68 with USPIOs. USPIO-related iron was distinguished from alternatively deposited iron by assessing MRI before and after USPIO application. Tissue affected by non-phagocytic inflammation during the first week mostly remained in a viably vital but remodeled state after 4 or 8 weeks, while phagocytic activity was associated with severe injury and necrosis accordingly. Conclusions: We conclude that the combined approach of USPIO-MRI and [ 11 C]PK11195-PET allows to observe post-stroke inflammatory processes in the living animal in an intraindividual and longitudinal fashion, predicting long-term tissue fate. The non-invasive imaging methods do not affect the immune system and have been applied to human subjects before. Translation into clinical applications is therefore feasible.